Carbon‐Coated Germanium Nanowires on Carbon Nanofibers as Self‐Supported Electrodes for Flexible Lithium‐Ion Batteries. Issue 23 (2nd February 2015) - Li, Weihan; Li, Minsi; Yang, Zhenzhong; Xu, Jun; Zhong, Xiongwu; Wang, Jiaqing; Zeng, Linchao; Liu, Xiaowu; Jiang, Yu; Wei, Xiang; Gu, Lin; Yu, Yan
<x xml:space="preserve">Abstract</x> A hybrid structure with carbon‐coated germanium nanowires grown on the surface of carbon nanofibers is fabricated using an in situ vapor–liquid–solid process. It is used as a self‐supported and flexible anode for Li‐ion batteries.